409. RECONSTRUCTION OF A SEGMENTAL OESOPHAGEAL DEFECT WITH A TUBED RADIAL ARTERY FOREARM FREE FLAP GUIDED BY 3-DIMENSIONAL MODELLING. (24th September 2022) - Leggett, Brandon; Bas, Onur; Wiper, Jonathan; Wagels, Michael; Frankel, Adam
Abstract: Segmental defects of the oesophagus are rare but complex. If the patient survives the initial insult, reconstructive techniques most commonly involve gastric pull-up or colonic interposition (1) however alternative techniques such as free flap reconstruction can be utilised if the former are unsuitable (2). The surgical field often is quite hostile in these cases, making pre-operative visualisation and planning critical in achieving a successful outcome. We describe our approach after a surgical complication in a 49-year-old man. cT3N2M0 GOJ adenocarcinoma, pre-operative FLOT4, three-stage oesophagectomy complicated by anastomotic leak and tracheo-gastric fistula. Cervical oesophagostomy and venting gastrostomy (via laparotomy) was performed (severe illness precluded one-lung ventilation). He improved and was discharged, but a persistent fistula from the gastric conduit to his trachea remained. Reconstruction was planned by a multidisciplinary team using detailed 3D modelling. Via right thoracotomy, the gastric conduit was reduced into the abdomen and the tracheal defect was repaired with an intercostal muscle flap. A retrosternal colonic interposition restored gastrointestinal continuity. The superior 2 cm infarcted and was replaced by a dual-paddled tubular radial forearm free flap. This complex surgical situation demonstrates how 3D visualisation of a segmental oesophageal defect can be extremely helpful in pre-operative planning. In particular, the precise anatomical location of the gastro-tracheal fistula and its relationship to the bony landmarks and surrounding vascular anatomy were critical in considering surgical access and reconstruction options. Whilst the literature describes applications of 3D visualisation for surgical planning in alternative contexts, there is minimal information of its use in upper gastrointestinal reconstruction. The use of 3D modelling and printing within the surgical context has frequently been associated with reduced operating times and improved medical outcomes (3). This case adds to the previously documented advantages of 3D modelling in surgical planning but applies them to an area not well covered in the literature. Additionally, it demonstrates the utility of an infrequently used technique (RAFF) for reconstructing a segmental oesophageal defect. Further research into quantifying the outcomes following the implementation of 3D modelling in visualisation and surgical planning would be useful in encouraging its integration into mainstream surgical practice.